2017
DOI: 10.3390/nu9060539
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants Involved in One-Carbon Metabolism: Polymorphism Frequencies and Differences in Homocysteine Concentrations in the Folic Acid Fortification Era

Abstract: Folate and other B vitamins are essential co-factors of one-carbon metabolism, and genetic variants, such as polymorphisms, can alter the metabolism. Furthermore, the adoption of food fortification with folic acid showed a decrease of homocysteine concentration. The aim of this study was to investigate the frequencies of the polymorphisms of enzymes and carrier proteins involved in one-carbon metabolism, and to evaluate homocysteine concentrations in the presence of these genetic variants in a population expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
0
10
0
1
Order By: Relevance
“…This reduced catalytic activity of MTHFR declines the production of 5-MTHF from folate. 5-MTHF is the active and circulating form of folate, which is a methyl donor for the conversion of homocysteine to methionine [ 12 , 30 , 31 ]. When methionine is converted back to homocysteine, the methyl group released causes DNA methylation [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…This reduced catalytic activity of MTHFR declines the production of 5-MTHF from folate. 5-MTHF is the active and circulating form of folate, which is a methyl donor for the conversion of homocysteine to methionine [ 12 , 30 , 31 ]. When methionine is converted back to homocysteine, the methyl group released causes DNA methylation [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown that hyperhomocysteinaemia is a well-known independent risk factor for atherosclerotic vascular disease and hypercoagulability states (72) . Studies have shown significant interactions between SNP involved in the C 1 metabolism pathway and dietary factors on homocysteine concentrations (73,74) . However, no studies, to date, have examined the interaction between C 1 metabolism-related genes and lifestyle factors on vitamin B 12 , folate and lipid concentrations.…”
Section: Findings From Genuine Collaborationmentioning
confidence: 99%
“…The global physical activity questionnaire was used to assess physical activity. Ten common SNP involved in the C 1 metabolism pathway were selected based on the published reports (74,7680) . The study identified significant interactions between the catechol-o-methyl transferase SNP (rs4680 and rs4633) and dietary carbohydrate intake on HDL-cholesterol concentrations ( P = 0·011 and 0·036, respectively).…”
Section: Findings From Genuine Collaborationmentioning
confidence: 99%
“…A common genetic variant in MTHFR is known to influence blood folate and prevalent in 10% of the population worldwide [85,86]. Steluti and colleagues studied polymorphism frequencies and differences in homocysteine concentrations even in the presence of folic acid fortification and found that homocysteine levels increased in those carrying genetic variants in folate metabolism, specifically in the MTHFR gene [87]. The prevalence of variant MTHFR TT has been found in 25% of Americans of Hispanic origin, 10-15% among white Americans, and only 0-1% for African Americans [77,[87][88][89].…”
Section: Folatementioning
confidence: 99%
“…Steluti and colleagues studied polymorphism frequencies and differences in homocysteine concentrations even in the presence of folic acid fortification and found that homocysteine levels increased in those carrying genetic variants in folate metabolism, specifically in the MTHFR gene [87]. The prevalence of variant MTHFR TT has been found in 25% of Americans of Hispanic origin, 10-15% among white Americans, and only 0-1% for African Americans [77,[87][88][89]. A review examining the nutritional deficiencies, bariatric surgery, and serum homocysteine levels found that the mutations of the MTHFR gene can be one of the reasons for persistent elevated serum homocysteine after surgery despite supplementation with B-group vitamins [76].…”
Section: Folatementioning
confidence: 99%